The Role of the Regional Government of Sampang Madura Regency in Managing Coastal Tourism as an Alternative Livelihood for Fishermen's Families - Helmy Boemiya,; Ida Wahyuliyana,; Boedi Mustiko,; Lutfy Susila Adi Irawan, (Technium Social Sciences Journal, 2023)
Referring to Law Number 7 of 2016 concerning Fishermen Protection and Empowerment, the purpose of the protection and empowerment of fishermen is provide infrastructure and facilities needed in developing business, provide certainty of sustainable business, and running independent, productive, advanced, modern and sustainable businesses. Folowing Articel 33 of 1945 Constitution Republik Indonesia The article seems to mandate the state and government to control natural resources and manage them for the prosperity of its people. The constitution above, has a clear constitutional basis related to protection and empowerment of fishermen. Utilizing the beauty of coastal tourism destinations, is gifts of extraordinary natural resources. Role of local government Coastal tourism-based tourism management by local government is expected to improve the economy of coastal communities, the majority of whom are fishermen. Regulations are the basis of tourism management which is legal umbrella for preparing coastal tourism development plans. Sampang Regency in development of coastal tourism, currently not only centered on the beach and results of fisheries or fishing in the sea. The development of coastal tourism potential in Sampang Regency expected to managed properly and sustainably by local government. Potential to improve economy, welfare community And alternative livelihood for fishing families.